Effects of Selective Harvesting on Diversity, Structure, and Regeneration of Woody Plants in Mixed Plantation of Menagesha Suba Forest, Central Ethiopia - Yigrem Workneh; Dessale Wasie (International Journal of Forestry Research)
This study was conducted at Menagesha Suba forest, central Ethiopia, with the aim of investigating the effects of selective harvesting on the diversity, structure, and regeneration of woody plants. As poorly and intensively implemented selective logging leads to rapid forest degradation, the selective harvesting at the study site overlooked the ecological sustainability of the forest. Vegetation data were collected using the systematic sampling method to establish a total of thirty-six nested plots, eighteen for each forest stand. The size of each main plot was 20 m × 20 m. Within each main plot, three subplots of size 5 m × 5 m were used for shrubs, and within the subplot, two 2 m × 2 m quadrants, each at the opposite corner, were used for seedling and sapling. The diameter and height of the individual tree having DBH >5 cm and height >2 m were measured using a diameter tape and hypsometer, respectively. Seedling with height <1 m and sapling with height 1–2 m were counted and measured for height using a marked stick. The result indicated that a total of 18 families and 27 species were identified in the harvested stand, while the corresponding values in the unharvested stand were 18 and 29, respectively. The value of species diversity, evenness, and richness in the unharvested stand was significantly higher (P<0.05) than in the harvested stand, but for native woody species, no significant difference (P>0.05) was observed in the species diversity and richness between the two forest stands. However, the evenness value of native species was significantly higher (P<0.05) in the unharvested stand than in the harvested stand. The stand structural analysis indicated that the mean basal area and volume of tree species in the unharvested stand were significantly higher (P<0.05) than in the harvested stand. However, no significant difference was observed in the mean density between the two forest stands. For native woody species, the mean value of the basal area, volume, and density of the unharvested stand was significantly higher (P<0.05) than in the harvested stand. The regeneration density was significantly higher (P<0.05) in the harvested stand than in the unharvested stand. However, for native woody species, no significant difference (P>0.05) was observed in the mean regeneration density between the two forest stands although an improved regeneration status was observed in the harvested stand. Overall, this study demonstrated that species group selective harvesting reduces the diversity and abundance of total woody species although the diversity of native woody species alone was not reduced. Harvesting also negatively affects the structure of the residual stand although the prolific sprout of Eucalyptus species from the logged stump favors the stand density. However, selective harvesting improves the regeneration of pioneer species. Therefore, it is recommended that species group selective harvesting should be carried out at intermediate intensity by technically skilled loggers to minimize the damage on the residual stand.